Modelling of random vertical irregularities of railway tracks - Podwórna, Monika (Zielona Góra: Uniwersytet Zielonogórski)
The study presents state-of-the-art in analytical and numerical modelling of random vertical irregularities of continuously welded ballasted railway tracks. The common model of railway track irregularity vertical profiles is applied, in the form of a stationary and ergodic Gaussian process in space. Random samples of track irregularity vertical profiles are generated with the Monte-Carlo method.
Keywords: ballasted railway track; continuously welded track; random vertical irregularities; track irregularities modeling; track irregularities random samples; Monte-Carlo method